Determinación de valores hematológicos y características morfocelulares de tortuga motelo (chelonoidis denticulata) en el eco zoológico San Martín en Baños de Agua Santa – Tungurahua. - Bilbao Medrano, Saskia Dayana (2022)
The objective of this research is to determine hematological values and morphocellular characteristics of the motelo tortoise (Chelonoidis denticulata) in the San Martin Eco Zoo in Baños de Agua Santa – Tungurahua. This was carried out through a descriptive observational croos sectional non design with a correlational approach, where 10 healthy appearing motelo tortoises were allocated, equally distributed between females and males, raised in captivity under the same housing conditions, health control and nutritionals diets. Blood samples were collected by brachial vein puncture, where hematological values were determined: erythrocytes 0.650.16 x 106/μL, hematocrit 26.84.78%, hemoglobin 9.931.59 g/dl, mean corpuscular volume 425.27fl, mean corpuscular hemoglobin 141.76pg and mean corpuscular hemoglobin concentration 33.33g/dl, leukocytes 2.740.93 x 103/μL, heterophils 34.2%, eosinophils 15.4%, basophils 6.8%, lymphocytes 42.8%, azurophiles 0.1%, monocytes 0.7% and thrombocytes 54.8%, where a small variation was observed in: decreased values in erythrocytes and leukocytes, high percentages of thrombocytes, heterophils and lymphocytes. In addition, the relationship of these values between male and female turtles was analyzed, where no statistically significant difference was found. Finally, the shape of the blood cells was described where the presence of immature erythrocytes and poikilocytes were found.